AJARAN KAMA PADA PATUNG SEKS DI PURA DALEM PURWA DESA PENGASTULAN KECAMATAN SERIRIT KABUPATEN BULELENG - Wardana, Kadek Agus (Institut Hindu Dharma Negeri Denpasar, 2019)
Kamasutra is seen by Hindus as an important book to guide human ethical life. This text beautifully describes the intimacy process of a pair of humans. An outline of the beliefs of Hinduism is love. Hinduism believes that the process of intimacy portrays a high human existence. The teachings are contained in the statue in the Dalem Purwa Temple where the statue depicting sex has a very deep meaning; these statues are not pornographic statues. But as a symbol of the merging of Lord Shiva?s strength with Dewi Parwati (Durga). It can also be interpreted as a symbol of the merging of Kama Bang with Kama Petak (Purusha with Pradhana). Where, there is a union of Shiva symbolized by Lingga with Parvati symbolized by Yoni that is where happiness arises, the emergence of prosperity, and prosperity. When kama bang (egg cell) with kama petak (sperm) meets resulting in fertilization that causes happiness and gives birth to a life of harmony. The meaning of philosophy is poured into statues with the scene of having sex as a symbol of unification. In Hindu sexuality is seen as sacred in human life because it is implicitly contained in purusartha chess teachings, namely dharma, artha, kama, and moksa. One of the goals of human life is the fulfillment of lust or desire (kama) which encourages people to do something, which makes people passionate in this life. One form of kama is fulfillment of sexual needs. The union of Lingga and Yoni gave birth to something new, namely creation. The combination of linga and yoni symbolizes the creation of the world and fertility.